Hubungan Status Gizi dan Anemia dengan Siklus Menstruasi pada Remaja Putri di Kecamatan Belimbing, Kabupaten Bangka - Bunga Romadhona Haque; Tami Ariati; Natalis Diyanti; Iriyanti Iriyanti; Sefti Ariyanti; Berti Novaria (Jurnal Ners, 2026)
Anemia and suboptimal nutritional status remain serious public health issues with high prevalence among adolescent girls in Indonesia. According to the World Health Organization (2021), approximately 30% of adolescent girls globally suffer from anemia, while the Indonesian Basic Health Research (Riskesdas) in 2018 reported that the prevalence of anemia among Indonesian adolescents reached 32%, with more than 25% experiencing undernutrition. These conditions directly affect reproductive health, particularly the regularity of the menstrual cycle. This study aims to examine the relationship between nutritional status and anemia in relation to the menstrual cycle among adolescent girls. A cross-sectional design was applied, involving 56 twelfth-grade female students from SMA Negeri 1 Belimbing. Data were collected through anthropometric measurements, hemoglobin level tests, and menstrual questionnaires. The analysis revealed that 55.36% of respondents had normal nutritional status, yet 51.79% were anemic. Spearman correlation tests showed no significant relationship between nutritional status or menstrual cycle and anemia; however, a statistically significant relationship was found between the duration of menstruation (p = 0.006) and menstrual blood volume (p = 0.002) and the incidence of anemia. These findings underscore the importance of routine screening and nutritional education programs targeting adolescent girls.